Fluorescent Multiplex Immunohistochemistry Coupled With Other State-Of-The-Art Techniques to Systematically Characterize the Tumor Immune Microenvironment - Boisson, Anaïs; Noël, Grégory; Saiselet, Manuel; Rodrigues-Vitória, Joël; Thomas, Noémie; Fontsa, Mireille Langouo; Sofronii, Doïna; Naveaux, Céline; Duvillier, Hugues; Craciun, Ligia; Larsimont, Denis; Awada, Ahmad; et al. (Frontiers in Molecular Biosciences, 2021)
Our expanding knowledge of the interactions between tumor cells and their microenvironment has helped to revolutionize cancer treatments, including the more recent development of immunotherapies. Immune cells are an important component of the tumor microenvironment that influence progression and treatment responses, particularly to the new immunotherapies. Technological advances that help to decipher the complexity and diversity of the tumor immune microenvironment (TIME) are increasingly used in translational research and biomarker studies. Current techniques that facilitate TIME evaluation include flow cytometry, multiplex bead-based immunoassays, chromogenic immunohistochemistry (IHC), fluorescent multiplex IHC, immunofluorescence, and spatial transcriptomics. This article offers an overview of our representative data, discusses the application of each approach to studies of the TIME, including their advantages and challenges, and reviews the potential clinical applications. Flow cytometry and chromogenic and fluorescent multiplex IHC were used to immune profile a HER2+ breast cancer, illustrating some points. Spatial transcriptomic analysis of a luminal B breast tumor demonstrated that important additional insight can be gained from this new technique. Finally, the development of a multiplex panel to identify proliferating B cells, Tfh, and Tfr cells on the same tissue section demonstrates their co-localization in tertiary lymphoid structures.